SMART Integrated Leadership (SMILE) for SmartCity - Septian Rheno Widianto; Rakhmadi Rahman (Jurnal Mantik, 2020)
The concept of a SmartCity which is becoming a big issue in big cities around the world encourages the active role and participation of the community in city management using a citizen centric approach so that there is a more dynamic and close interaction between citizens and service providers. The aim of implementing a SmartCity is to be able to form and implement a city that is safe, comfortable, controlled and facilitates access for its citizens and strengthens the competitiveness of the city in terms of economy, social and technology. SmartCity must have a strong governance-oriented approach that emphasizes the role of social capital and relationships in urban development. The Smart City concept is no longer limited to ICT diffusion, but looks at people and society's needs. To meet and exceed citizen expectations, city leaders must innovate in core service areas in the application of the SmartCity concept. In order to create innovative, creative and resilient leaders, it is necessary to design a Smart Integrated Leadership (SMILE) to support the success of a SmartCity.